Structural and Kinetic Effects of PAK3 phosphorylation mimic of cTnI(S151E) on the cTnC-cTnI Interaction in the Cardiac Thin Filament - Ouyang, Yexin (2010)
Residue Ser151 of cTnI is known to be phosphorylated by p21-activated kinase 3 (PAK3). It has been found that PAK3-mediated phosphorylation of cTnI induces an increase in myofilament Ca(2+) sensitivity, but the detailed mechanism is unknown. We investigated how the structural and kinetic effects mediated by pseudo-phosphorylation of cTnI (S151E) modulates Ca(2+)-induced activation of cardiac thin filaments. Using steady-state, time-resolved Förster Resonance Energy Transfer (FRET) and stopped-flow kinetic measurements, we monitored Ca(2+)-induced changes in cTnI-cTnC interactions. Measurements were done using reconstituted thin filaments, which contained the pseudo-phosphorylated cTnI(S151E). We hypothesized that the thin filament regulation is modulated by altered cTnC-cTnI interactions due to charge modification caused by the phosphorylation of Ser151 in cTnI. Our results showed that the pseudo-phosphorylation of cTnI (S151E) sensitizes structural changes to Ca(2+) by shortening the intersite distances between cTnC and cTnI. Furthermore, kinetic rates of Ca(2+) dissociation-induced structural change in the regulatory region of cTnI were significantly reduced by cTnI (S151E). The aforementioned effects of pseudo-phosphorylation of cTnI were similar to the effects of strong crossbridges on structural changes in cTnI. Our results provide novel information on how cardiac thin filament regulation is modulated by PAK3 phosphorylation of cTnI.